Intergenerational Programs and Practices in China: Results Based on a Web Search Method: Research. Issue 1 (2nd January 2020) - Li, Qiao; Kaplan, Matthew; Thang, Leng Leng
ABSTRACT: In the midst of an aging population trend and increased concerns about elder care, the Chinese government has developed policies that aim to strengthen family support systems and ensure older adult engagement in community life. One domain of related intervention that has received relatively little attention and systematic study in China is in the area of intergenerational programming. To gain a sense of the breadth and types of intergenerational programs emerging in China, the authors employed a web search method utilizing Google and Baidu search engines. Findings indicate a fair amount of program innovation and diversity as well as a need for additional programmatic and policy measures to strengthen and support intergenerational relationships in family and community contexts.